WARALABA (FRANCHISE) SEBAGAI SARANA PENGEMBANGAN USAHA KECIL (SUATU TINJAUAN HUKUM) Franchise as Means of Small Business Development (A Legal View) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT The objectives of this study are to identify the implementation of franchise system as a partnership between large or medium business and small ones, to identify the relationship between large or medium business being franchisor and small business as franchisee, as well as to idenlifity governmental intervention and supervision upon the implementation of franchise system as a cooperation of large or medium business and small ones. The study was conducted to obtain both primary and secondary data. Secondary data were obtained through library research that was the analysis of documents on particular subjects. Primary data were collected from a field study making use of questionaires and interviews. Questionaires included both transparent and confidential ones, that the data obtained were focused and comprehensive. Interviews were carried out with list of questions. Questionaires were distributed to a number of 30 compaines. Interviews were addressed to 5 informants and some respondents to fill up the questionaires. Interviews were addressed to informants and some respondents to fill up the questionaires. The respondents consisted of two groups of franchisors and both franchisees and potential franchisees. The study suggested the following results: 1. The relationship of large or medium business as franchisor and small business as franchisee was firm and interrelated, and it had 2 (two) aspects: relational and formal. a. The relational aspect comes from cooperation based on the operational relationship. The cooperation between franchisor and franchisee is special and is different from most business relationship. There is an analogy tobe drawn between parent- child relations on the one hand and franchisor - franchisee relations on the other. . The formal aspect comes from the cooperation based on the franchising arrangements. The mechanism of the cooperation is based on the principles of equality and mu tualism. 2. The partnership pattern between large or medium business as franchisor and small business as- franchisee was based upon contract which resulted in mutual rights and obligations for the parties in cooperation, so that the act of giving intellectual properties and distribution line by the franchisee would present obligations to the franchisee in the form of royalty payment. In the case of partnership between large or medium business and small ones, though transparent and voluntary, it should be m accordance to the principles of mutual necessities, mutual empowerment and mutual benefit (Article 1 Paragraph 1 of Government Regulation on Partnership). 3. Franchise was not merely an agreement between franchisor and franchisee but it was a commercial partnership with objectives of minimizing market domination by large business, thus governmental intervention was required. The governmental role was not necessarily to change civil status of franchise to public or semi-public. Keywords: franchise -- partnership â small business